High Prevalence of Soil-Transmitted Helminths Without Concomitant Anemia: A Cross-Sectional Study of Children in an Indonesian Urban Waste Disposal Site - Ka’bah; Risma Yuliana (Scientific Journal of Pediatrics, 2024)
Introduction: Soil-transmitted helminth (STH) infections are a dominant cause of morbidity, particularly anemia, in pediatric populations in low-resource settings. Children residing in urban waste disposal sites ("Tempat Pembuangan Akhir" - TPA) represent a uniquely vulnerable, under-studied population. This study investigates the paradoxical relationship between STH infection, hematological status, and iron reserves in children living at the TPA Tamangapa, Makassar, Indonesia. Methods: A cross-sectional study was conducted involving 120 children aged 5-10 years. Sociodemographic and hygiene data were collected via a structured questionnaire. Stool samples were analyzed using the quantitative Kato-Katz technique (duplicate slides) to determine STH prevalence and infection intensity (Eggs Per Gram - EPG). Venous blood was analyzed for complete blood count (CBC) using an automated hematology analyzer and for iron status (serum ferritin, serum iron, TIBC) via ELISA and colorimetric assays. Statistical analysis included descriptive statistics, Chi-square tests, t-tests, and logistic regression to identify associations. Results: The overall prevalence of STH infection was 55.0% (66/120). Ascaris lumbricoides was the most common infection (25.0%), followed by Trichuris trichiura (15.0%) and co-infections (15.0%). The majority of infections (86.4%) were of light-to-moderate intensity. Overt anemia (Hb < 11.5 g/dL) was rare and its prevalence was not significantly different between infected (10.6%) and non-infected (9.3%, p=0.814) children. Mean hemoglobin levels were statistically indistinguishable (12.4 g/dL vs. 12.6 g/dL, p=0.082). However, STH-infected children demonstrated significantly depleted iron stores: mean serum ferritin was 28.5 ng/mL versus 47.2 ng/mL in non-infected children (p<0.001). Consequently, iron depletion (ferritin < 20 ng/mL) was epidemic in the infected group (43.9%) compared to the non-infected group (7.4%, p<0.001). Conclusion: In this high-risk population, STH prevalence is high but is not associated with overt anemia. This paradox is resolved by comprehensive analysis revealing a strong, significant association with depleted iron stores. This "hidden morbidity" of iron depletion, undetectable by simple hemoglobin screening, underscores the need for integrated WASH (Water, Sanitation, Hygiene) programs and more sophisticated iron-status screening in high-risk pediatric populations.